By definition, the formula to find a Midpoint is:
![M=((x_1+x_2)/(2)+(y_2-y_1)/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/eh8t5y126ldgv8uckc13w5dh1uw5ye0c0n.png)
Where the coordinates of the first point are:
![(x_1,y_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/x550ag71r3nlvmk4as4e3r7sboim1mls0a.png)
And the coordinates of the second point is:
![(x_2,y_2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/g2xe4697c8nj96m3ga7mj2jg9gkhu2oo18.png)
Let be the coordinates of the Midpoint:
![(x_M,y_M)](https://img.qammunity.org/2023/formulas/mathematics/college/a1ubfwc910m5ir2muqndj8ci49olz9akvt.png)
In this case, knowing coordinates of the point A and the Midpoint, you can set up the following equations:
- Equation 1:
![x_M=(x_A+x_B)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/3i2m8srqi2kcojer02z8sp8n0v8v7997hx.png)
- Equation 2:
![y_M=(y_A+y_B)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/t4itw95q7hlayey2h9vqhtsp5kuiu91b24.png)
Choose the Equation 1, substiutute values and solve for x-coordinate of the endpoint B:
![\begin{gathered} x_M=(x_A+x_B)/(2) \\ \\ 2=(-3+x_B)/(2) \\ \\ (2)(2)=-3+x_B \\ 4+3=x_B \\ x_B=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o8skymxtn1qlowv0sgs4j1oypf582dj90d.png)
Now choose the Equation 2 and solve for the y-coordinate of the point B:
![\begin{gathered} y_M=(y_A+y_B)/(2) \\ \\ -1=(-5+y_B)/(2) \\ \\ (-1)(2)=-5+y_B \\ -2+5=y_B \\ y_B=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d6flmec4yaq1p3xjiel63yt9lbct41vl2z.png)
Therefore, the coordinates of P are:
![B(7,3)](https://img.qammunity.org/2023/formulas/mathematics/college/tzckt5tlusd0q0naxxrvwbqz287obqrlcm.png)